A dictionary of genetics - King, Robert C (Oxford University press, 2002)
Genetics has entered a new era with the advent of genomic and proteomic approaches, and the knowledge in no other biological discipline is advancing as rapidly as that in molecular genetics and cell biology. Proliferation of new terms inevitably accompanies such exponential growth.